Fear of falling and its association with life-space mobility of older adults: a cross-sectional analysis using data from five international sites - Auais, Mohammad (Age Ageing, 2017)
BACKGROUND: fear of falling (FOF) is a major health concern among community-dwelling older adults that could restrict mobility. OBJECTIVE: to examine the association of FOF with life-space mobility (i.e. the spatial area a person moves through in daily life) of community-dwelling older adults from five diverse sites. METHODS: in total, 1,841 older adults (65–74 years) were recruited from Kingston, Canada; Saint-Hyacinthe, Canada; Tirana, Albania; Manizales, Colombia and Natal, Brazil. FOF was assessed using the Fall Efficacy Scale-International (FES-I total score), and the life space was quantified using the Life-Space Assessment (LSA), a scale that runs from 0 (minimum life space) to 120 (maximum life space) RESULTS: the overall average LSA total score was 68.7 (SD: 21.2). Multiple-linear regression analysis demonstrated a significant relationship of FOF with life-space mobility, even after adjusting for functional, clinical and sociodemographic confounders (B = −0.15, 95% confidence interval (CI) −0.26 to −0.04). The FOF × site interaction term was significant with a stronger linear relationship found in the Canadian sites and Tirana compared with the South American sites. After adjusting for all confounders, the association between FOF with LSA remained significant at Kingston (B = −0.32, 95% CI −0.62 to −0.01), Saint-Hyacinthe (B = −0.81, 95% CI −1.31 to −0.32) and Tirana (B = −0.57, 95% CI −0.89 to −0.24). CONCLUSION: FOF is an important psychological factor that is associated with reduction in life space of older adults in different social and cultural contexts, and the strength of this association is site specific. Addressing FOF among older adults would help improve their mobility in local communities, which in turn would improve social participation and health-related quality of life.